Respiratory health screening for opiate misusers in a specialist community clinic: a mixed-methods pilot study, with integrated staff and service user feedback. Issue 10 (14th October 2016) - Mitchell, Caroline Anne; Pitt, Alice; Hulin, Joe; Lawson, Rod; Ashby, Fleur; Appelqvist, Ivan; Delaney, Brigitte
Abstract : Objectives: Increased rates of illicit drug inhalation are thought to expose opiate misusers (OMUs) to an enhanced risk of respiratory health problems. This pilot study aimed to determine the feasibility of undertaking respiratory screening of OMUs in a community clinic. Setting: Single-centre UK community substance misuse clinic. Participants: All clinic attendees receiving treatment for opiate misuse were eligible to participate. 36 participants (mean age=37) were recruited over a 5-week period. The sample included 26 males and 10 females. Outcome measures: Spirometry without bronchodilation; health related quality of life EQ-5D-3L; Asthma Control Test; Mini Asthma Quality of Life; Clinical COPD Questionnaire and the Treatment Outcome Profile were used to assess the respiratory health of participants. Findings were discussed with staff and service users in 2 patient and public involvement events and feedback was analysed thematically. Results: 34 participants reported that they had smoked heroin. 8 participants diagnosed with asthma, scored under 13 on the Asthma Control Test, suggesting poorly controlled asthma. Participants (n=28), without a diagnosis of asthma completed the Lung Function Questionnaire. Of these, 79% produced scores under 18, indicating symptoms associated with the development of chronic obstructive pulmonary disease. Spirometry showed 14% of all participants had forced expiratory volume in 1 s/forced vital capacity <0.7 (without bronchodilator), indicating potential obstructive lung disease. Feedback from service users and staff suggested a willingness and capacity to deliver respiratory health screening programmes. Insight towards the difficulties service users have in accessing services and the burden of respiratory health was also provided. Conclusions: It is feasible to undertake respiratory health screening of OMUs in a community clinic. Larger screening studies are warranted to determine the prevalence of respiratory health problems in this population. Research regarding asthma medicines adherence and access to healthcare among OMUs is also required.